The Influence of Profitability, Liquidity, Interest Rates, and Inflation on Bond Ratings Listed on the Indonesia Stock Exchange - Talitha Nabila Sari; Lina Budiarti (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of profitability, liquidity, interest rates, and inflation on bond ratings of industrial sector companies listed on the Indonesia Stock Exchange for the 2021–2023 period. The method used is a quantitative approach with logistic regression analysis, where the data were obtained through documentation of financial reports and bond rating data from the official websites of the IDX and PEFINDO. The test results show that simultaneously, the independent variables have a significant effect on bond ratings. Partially, the variables of interest rates and inflation are proven to have a significant effect on bond ratings, while profitability and liquidity do not have a significant effect on bond ratings. These findings confirm that macroeconomic conditions such as interest rates and inflation play a more dominant role in influencing bond ratings compared to the internal performance of companies. This research is expected to serve as a reference for investors and companies in making investment decisions in the bond market.